OTORITAS JASA KEUANGAN DAN KIPRAHNYA DI KOTA PALU - Murniati Ruslan (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
The establishment of Financial Service Authority (FSA) is a mandate of Law No 21 Year 2011 about Financial Service Authority. FSA is a state institution that is responsible for supervising finance such as bank or non-bank financial service institution, videlicet insurance company, finance company, pension funds and capital markets. This research studies FSA in Central Sulawesi province which has stints as commanded by constitution. It is then able to be seen from the number of public complaints handled since in this province is formed at 1st January 2014. Central Sulawesi FSA Office obtained 70 cases from financial service industry costumers as well as sufficient incentive to introduce micro-finance institutions to disseminate Act No. 1 of 2013 on Micro Financial Institutions (MFIs) as an institution in the community economic development efforts. Moreover, the leader of FSA Office Central Sulawesi keeps making serious efforts to strengthen the institution in order to improve and amplify FSA Office’s oversight function hence it embraces conventional bank, Islamic bank and non-bank financial institution besides continues to encourage the establishment of novel offices by facilitating license (inter alia, opening one door service). This studies also discovers some matters faced by FSA Office Center Sulawesi these days; the quantity and quality of human resources.